Implementasi Alat Mentoring Suhu Dan Kelembaban Kandang Bebek Di Peternakan Tanjung Morawa Berbasis Mikrokontroler - Masdania Zurairah; Muhammad Adam; Partaonan Harahap (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
This new discovery arose because the dilator is backed by high work efficiency, as well as the effectiveness and efficiency of human labor in carrying out the manual (hand) process. Therefore, a thought emerged to make a special cage for ducks that can control temperature, humidity and feed automatically by using solar panels as an energy source. The method used is solar panels converting energy which is then stored in the battery by the solar charger controller. The battery then supports a load consisting of the main device, namely a 60WP solar panel, 12 7AH VRLA battery, 20A Solar Charger Controller and DC to DC Converter Step Down. This research starts from 08:30 - 15:30. The results of the research on the Solar Power Plant are 19.4 Watts of power, 1.4A current, and 13.87V connections.